1998
DOI: 10.1038/sj.bmt.1701287
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor leads to reduced blood processing during apheresis or the use of whole blood aliquots to support dose-intensive chemotherapy

Abstract: Summary:The addition of stem cell factor (SCF) to G-CSF and chemotherapy results in a dose-dependent, significantly increased mobilisation of peripheral blood progenitor cells compared with the use of chemotherapy and G-CSF alone. The enhanced mobilisation may benefit patients in several ways. Firstly, in clinical settings where currently multiple aphereses are having to be performed to obtain a specified target number of cells, the addition of SCF may lead to a reduction in this number. Alternatively, when on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…3 Various authors have demonstrated that it is also possible to effectively mobilize 2.0 ϫ 10 6 CD34-positive cells per kg into 500-1000 ml of whole blood. [4][5][6][7] So far, WB has been successfully applied after high-dose chemotherapy for multiple myeloma, non-Hodgkin's lymphoma and lung cancer. [8][9][10] However, a major disadvantage of WB is that the storage time is very limited.…”
mentioning
confidence: 99%
“…3 Various authors have demonstrated that it is also possible to effectively mobilize 2.0 ϫ 10 6 CD34-positive cells per kg into 500-1000 ml of whole blood. [4][5][6][7] So far, WB has been successfully applied after high-dose chemotherapy for multiple myeloma, non-Hodgkin's lymphoma and lung cancer. [8][9][10] However, a major disadvantage of WB is that the storage time is very limited.…”
mentioning
confidence: 99%
“…The median interval between the last day of mobilization chemotherapy and the first apheresis was 10 days (8)(9)(10)(11)(12)(13)(14) for the IFO+GM-CSF group and 13 days (8-25) for the CY+GM-CSF group (P = 0.002). GM-CSF was administered for a median of 9 days (7-13) and 15 days (9-31), respectively (P = 0.001).…”
Section: Leukapheresis Mononuclear Cell and Cd-34 + Yieldmentioning
confidence: 99%
“…3 However, the frequency of progenitors in the peripheral blood under steady-state conditions is extremely low, making the harvest very costly and cumbersome to obtain enough PBPC for transplantation. 4 Chemotherapy with or without the addition of growth factors such as G-CSF, 5 GM-CSF, 6 interleukin 3 7 or stem cell factor 8 is able to increase the number of PBPC. High-dose cyclophosphamide alone 9 (4-7 g/m 2 ) or followed by G-CSF 10 or GM-CSF 11 is a frequently used regimen for PBPC mobilization but it is not exempt from morbidity.…”
mentioning
confidence: 99%
“…In this latter group it is possible that the mobilisation seen is related solely to the chemotherapy used for mobilisation in conjunction with G-CSF rather than to the combined effect. Alternatively, it is also possible that the dose of 5 g/kg of G-CSF represents maximum stimulation for the G-CSF-sensitive cells whereas the patients with increased CD34-positive cell levels are capable of responding to higher doses of G-CSF With the advent of new cytokines with significant mobilisation ability 5 it will be important to evaluate these agents in conjunction with assessments of prior chemotherapy in order to identify optimal mobilisation techniques for the greatest number of patients possible.…”
Section: Poor Stem Cell Mobilisers -Variation In Response To G-csf Domentioning
confidence: 99%